ANALISIS LAGU TORAJA MARENDENG MARAMPA ARANSEMEN TINDOKI BAND - Lamba, Linesti; Ardini, Ni Wayan; Darmayuda, I Komang; Sumerjana, Ketut (Journal of Music Science, Technology, and Industry, 2019)
This study aims to describe the musical form of Marendeng Marampa'", a local song in Toraja, Tana Toraja Regency, South Sulawesi Province, Indonesia, arranged by the Tindoki Band. The qualitative data in this research are obtained by doing observation, interviews, documentation, and discography. The results of this research show that " Marendeng Marampa'" arranged by Tindoki Band have two parts, i.e. the form A-B, with the sequence A-A' A-A-A'-B-B-B" consisting of several figures, motives, phrases (antecedent phrase and consequent phrase). Its musical instruments used in this arrangement are collaboration between the traditional musical instruments in Toraja, including Toraja gandang, Toraja flute, basin bassin/tulali, karombi, and modern (Western) music, i.e. electric guitar, bass guitar, keyboard, and electric drums, which lyrics are incorporated into the arrangement of Ma'bugi and Manimbong. Marendeng Marampa'" means safe, peaceful land of birth and is also a unifying song for the people of Toraja. The song is a reminiscent for the people of Toraja to remind their home region that tondok kadadian is their land of birth.